The Causal Role of Mitochondrial Dynamics in Regulating Insulin Resistance in Diabetes: Link through Mitochondrial Reactive Oxygen Species. (30th September 2018) - Lin, Hung-Yu; Weng, Shao-Wen; Chang, Yen-Hsiang; Su, Yu-Jih; Chang, Chih-Min; Tsai, Chia-Jen; Shen, Feng-Chih; Chuang, Jiin-Haur; Lin, Tsu-Kung; Liou, Chia-Wei; Lin, Ching-Yi; Wang, Pei-Wen
Abstract : Background . Mitochondrial dynamics (mtDYN) has been proposed as a bridge between mitochondrial dysfunction and insulin resistance (IR), which is involved in the pathogenesis of type 2 diabetes (T2D). Our previous study has identified that mitochondrial DNA (mtDNA) haplogroup B4 is a T2D-susceptible genotype. Using transmitochondrial cybrid model, we have confirmed that haplogroup B4 contributes to cellular IR as well as a profission mtDYN, which can be reversed by antioxidant treatment. However, the causal relationship between mtDYN and cellular IR pertaining to T2D-susceptible haplogroup B4 remains unanswered. Methods . To dissect the mechanisms between mtDYN and IR, knockdown or overexpression of MFN1, MFN2, DRP1, and FIS1 was performed using cybrid B4. We then examined the mitochondrial network and mitochondrial oxidative stress (mtROS) as well as insulin signaling IRS-AKT pathway and glucose transporters (GLUT) translocation to plasma membrane stimulated by insulin. We employed Drp1 inhibitor, mdivi-1, to interfere with endogenous expression of fission to validate the pharmacological effects on IR. Results . Overexpression of MFN1 or MFN2 increased mitochondrial network and reduced mtROS, while knockdown had an opposing effect. In contrast, overexpression of DRP1 or FIS1 decreased mitochondrial network and increased mtROS, while knockdown had an opposing effect. Concomitant with the enhanced mitochondrial network, activation of the IRS1-AKT pathway and GLUT translocation stimulated by insulin were improved. On the contrary, suppression of mitochondrial network caused a reduction of the IRS1-AKT pathway and GLUT translocation stimulated by insulin. Pharmacologically inhibiting mitochondrial fission by the Drp1 inhibitor, mdivi-1, also rescued mitochondrial network, reduced mtROS, and improved insulin signaling of diabetes-susceptible cybrid cells. Conclusion . Our results discovered the causal role of mtDYN proteins in regulating IR resulted from diabetes-susceptible mitochondrial haplogroup. The existence of a bidirectional interaction between mtDYN and mtROS plays an important role. Direct intervention to reverse profission in mtDYN provides a novel therapeutic strategy for IR and T2D.